THE EFFECT OF ABDOMINAL STRETCHING EXERCISE ON THE REDUCTION OF PRIMARY DYSMENORRHEA AT MUHAMMADIYAH VOCATIONAL SCHOOL, PALEMBANG - Mar'atun Ulaa; Murbiah Murbiah; Debby Sahara Dance; Mareta Kurniati (Universitas Muhammadiyah Kudus, 2022)
AbstrakMenstruation is the process of bleeding from the uterus that occurs due to the shedding of the unfertilized uterine lining. During menstruation some women experience discomfort in their bodies, especially in the lower abdomen. Dysmenorrhea is pain in the lower abdominal muscles, radiating to the waist and inner thighs , before or during menstruation due to uterine muscle contractions. Dysmenorrhea occurs due to an increase in prostaglandins that trigger uterine muscle contractions, so that the blood vessels in the uterus narrow. Dysmenorrhea can cause a decrease in adolescent concentration while studying, affect activities and make learning achievement decline. Abdominal Stretching Exercise is a muscle stretching exercise in the abdomen to increase muscle strength, endurance, and flexibility so that it is expected to reduce dysmenorrhea . This research is a quantitative study using a Quasi-Experiment Design with a Pre-Test and Post-Test Non-Equivalent Control Group Design. Respondents in this study were 44 respondents consisting of 22 respondents as the intervention group and 22 respondents as the control group . The results showed that in the intervention group the mean pretest value was 6.45, while the mean posttest was 4.32. In addition, the mean value of the control pretest was 5.41, while the mean value of the control posttest was 4.46. Mark pValue of the intervention group (0.000) = 0.05 and pValue of the control group (0.000) = 0.05. Abdominal Stretching Exercise has an effect on reducing primary dysmenorrhea.